Sufism-Based Education and Students’ Moral Development in Islamic Schools: A Case Study of Madrasah Tsanawiyah Nadhatul Uluma - Akhmad Khamdani; M. Imdadur Rohman; Lora Hilal Fikri; Samsul Arifin; Aan Miftakhul Fawaid (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This research stems from the urgent need to strengthen moral education in the era of globalisation, which is characterised by a value crisis and a weakening of the internalisation of religious ethics among students, particularly in the context of Islamic boarding school-based education. The purpose of this study is to analyse the implementation of Sufi-based education in shaping the moral development of students at MTs NU Sindujoyo Gresik. This study uses a qualitative approach with a case study design, utilising data collection techniques such as participant observation, in-depth interviews, and documentation. Data analysis was conducted using the perspective of Islamic spiritual education and the theory of value internalisation. The results of the study indicate that the integration of Sufi values based on Islamic boarding school culture, the exemplary behaviour of teachers and kiai, and routine spiritual activities such as Dhuha prayer, Dhuhr prayer in congregation, dhikr, and istighasah play an important role in forming a conducive educational ecosystem. Values such as tazkiyat al-nafs, muraqabah, ikhlas, and Mahmudah morals are effectively internalised in the lives of students. The findings demonstrate an improvement in students' moral character, including discipline, responsibility, social empathy, and self-control, through a synergy between the formal curriculum, the hidden curriculum, and Islamic boarding school culture. Sufi-based education focuses not only on cognitive aspects but also brings about profound moral and spiritual transformation, making it a relevant model for integrative and adaptive Islamic education.